Lip Prominence Using Different Reference Planes - Pradhan, Resina; Rajbhandari, Anjana; Bajracharya, Manju; Manandhar, Pushkar; Maharjan, Surendra (Orthodontic Journal of Nepal, 2019)
Introduction: Facial beauty lies on lip prominence which in turn is the reflection of dental and skeletal relation of the jaws beside the lip morphology. Thus, orthodontist has control over lip prominence to enhance beauty by altering skeletal and dental relation. Hence analyzing lip prominence is essential for the success of orthodontic treatment. The aim of the present study is to determine lip prominence using different reference planes and secondly to assess sexual differences in lip prominence. Materials & Method: lateral cephalograms of 43 (23 males and 20 females) Brahmins aged 18 - 27 years were collected. They were having dentally: Angle’s Class I molar and canine relation with normal overjet and overbite and skeletally: normal jaw relationship, symmetric face with acceptable facial profile, without craniofacial abnormalities. Linear distance was measured in lateral cephalograms from most prominent point of the lip to reference planes of different analysis system. Comparative test was conducted within Brahmins to check gender diversity at significance level p ≤ 0.05. Result: Comparison of lip prominence of male and female Brahmins were found to have no statistically significant differences except for the upper lip to Burstone B line (p ≤ 0.05) and lower lip to Holdaway H line (p ≤ 0.05). When means of males and females were compared males were found to have more protrusive lips. The Result of this study indicates protrusive lips of Brahmins compared to the established norms of Caucasians as analyzed with reference plane of different analysis system namely Ricketts, Steiners and Burstones. Sushners analysis showed retrusive lips indicating retrusive lips of Brahmins as compared with Black population. Conclusion: During orthodontic treatment planning lip prominence should be emphasized based on gender and ethnicity.